89Zr Immuno-PET Imaging of Tumor PD-1 Reveals That PMA Upregulates Lymphoma PD-1 through NFκB and JNK Signaling - Jung, Kyung-Ho; Lee, Jin Hee; Kim, Mina; Cho, Young Seok; Lee, Kyung-Han (Molecular imaging, 2022)
Immune therapy of T-cell lymphoma requires assessment of tumor-expressed programmed cell death protein-1 (PD-1). Herein, we developed an immuno-PET technique that quantitatively images and monitors regulation of PD-1 expression on T-cell lymphomas. Methods. Anti-PD-1 IgG underwent sulfhydryl moiety-specific conjugation with maleimide-deferoxamine and 89Zr labeling. Binding assays and Western blotting were performed in EL4 murine T-cell lymphoma cells. In vivo pharmacokinetics, biodistribution, and PET were performed in mice. Results. 89Zr-PD-1 IgG binding to EL4 cells was completely blocked by cold antibodies, confirming excellent target specificity. Following intravenous injection into mice, 89Zr-PD-1 IgG showed biexponential blood clearance and relatively low normal organ uptake after five days. PET/CT and biodistribution demonstrated high EL4 tumor uptake that was suppressed by cold antibodies. In EL4 cells, phorbol 12-myristate 13-acetate (PMA) increased 89Zr-PD-1 IgG binding (305.5±30.6%) and dose-dependent augmentation of PD-1 expression (15.8±3.8−fold of controls by 200 ng/ml). FACS showed strong PD-1 expression on all EL4 cells and positive but weaker expression on 41.6±2.1% of the mouse spleen lymphocytes. PMA stimulation led to 2.7±0.3-fold increase in the proportion of the strongest PD-1 expressing EL4 cells but failed to influence that of PD-1+ mouse lymphocytes. In mice, PMA treatment increased 89Zr-PD-1 IgG uptake in EL4 lymphomas from 6.6±1.6 to 13.9±3.6%ID/g (P=0.01), and tumor uptake closely correlated with PD-1 level (r=0.771, P<0.001). On immunohistochemistry of tumor sections, infiltrating CD8α+ T lymphocytes constituted a small fraction of tumor cells. The entire tumor section showed strong PD-1 staining that was even stronger for PMA-treated mice. Investigation of involved signaling revealed that PMA increased EL4 cell and tumor HIF-1α accumulation and NFκB and JNK activation. Conclusion. 89Zr-PD-1 IgG offered high-contrast PET imaging of tumor PD-1 in mice. This was found to mostly represent binding to EL4 tumor cells, although infiltrating T lymphocytes may also have contributed. PD-1 expression on T-cell lymphomas was upregulated by PMA stimulation, and this was reliably monitored by 89Zr-PD-1 IgG PET. This technique may thus be useful for understanding the mechanisms of PD-1 regulation in lymphomas of living subjects.